The postscript murders - Griffiths, Elly (Houghton Mifflin Harcourt, 2021)
"Murder leaps off the page when crime novelists begin to turn up dead in this intricate new novel by internationally best-selling author Elly Griffiths, a literary mystery perfect for fans of Anthony Horowitz and Agatha Christie"--